Endogenous labor share cycles: theory and evidence - Jakub Growiec; Peter McAdam; Jakub Muck (European Central Bank (ECB), 2015)
Based on long US time series we document a range of empirical properties of the labor's share of GDP, including its substantial medium-run swings. We explore the extent to which these empirical regularities can be explained by a calibrated micro-founded long-run economic growth model with normalized CES technology and endogenous labor- and capital-augmenting technical change driven by purposeful directed R&D investments. It is found that dynamic macroeconomic trade-offs created by arrivals of both types of new technologies may lead to prolonged swings in the labor share due to oscillatory convergence to the balanced growth path as well as stable limit cycles via Hopf bifurcations. Both predictions are broadly in line with the empirical evidence.
Keywords: E25; E32; O33; O41; 330; CES; endogenous cycles; factor-augmenting endogenous technical change; labor income share; normalization; R&D; technology menu